Reproductive Performances of SIMGOUD Crossbreed Cows and The Effect of Concentrate Feed Supplementation on The Production and Chemical Composition of Milk - Mama Mouchili; Edouard Aimé Pouachiyouen Pechangou; Emile Miegoué; Jules Lemoufouet; Fernand Tendonkeng (Journal of Applied Veterinary Science And Technology, 2024)
Background: The performance of milk production remains very weak.  This low performance is mainly explained by the low genetic potential of local breeds (1 to 3 litre of milk/day or even less in the dry season compared to 40 to 50 l/day for Holstein cows in Europe).  Purpose: The present study on the evaluation of the reproductive performance of Simgoud crossbreed cows and the effect of feeding on the production and chemical composition of milk was conducted at the SODEPA ranch of Faro in Adamaoua Cameroon between July and August 2023.  Method:  The Simgoud cow is a cross between the exotic Simmental and the local Goudali breeds. The animals were divided into two batches of six cows and six calves per batch, of comparable physiological condition. Results:  The age at first calving was 39 months, and the crossbreeding allowed the farmer to decrease the age at first calving of the Goudali by 24%. The observed calving interval was 18 months with a variation rate of 16.20%. The total amount of milk produced in 90 days by the cows that received a feed supplement (concentrate) was estimated at 810 liters for an average daily production of 9.66 liters, compared to 666 liters over the same lactation period in the cows that did not receive a supplement, an average of 7.46 liters per day. Supplementation had a significant effect on milk production. The analysis of the chemical composition of the milk shows that apart from the pH, the supplementation of Simgoud cows with concentrate had a significant effect, improving the content of all other parameters studied. Conclusion:  Supplementation is recommended for the improvement of the milk production parameters in Simgoud cows.